Adolescent upbringing as related to the self-concept of Maranao high school students - Manonggiring, Raga Mansongayan 1955- (1987)
The objective of the study is to find out the relationships between adolescent upbringing and self-concept of Maranao high school students. The study reveals that out of the six personal characteristics of the respondents, namely, civil status, sex, age, general weighted average, year level and birth order, only the general weighted average is significantly related to the negative upbringing indicators of punishment and permissiveness among Maranao parents and civil status is significantly related to the positive upbringing indicators of love and control. The study hopes to serve as a self-evaluative guide to Maranaos in accepting adolescent upbringing that positively leads to the development of better self-concept among them.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Child rearing; Self-perception.